Caracterização e processamento da carne de jacaré-do-Pantanal (Caiman yacare) : composição físico-química e rendimento - Fernandes, Vitória Regina Takeuchi (2011)
The present study had the objective to evaluate the quality of the meat of the Pantanal caiman (Caiman yacare) and verifying the potential for the development of different products. Were used 20 animals with average weight of 3.585 kg from the Pantanal Breeders Cooprative, authorized by the Brazilian Institute of the Environment and Natural Resources (Ibama), located in the town of Cáceres - MT. In the first experiment, four commercial cuts from females and males were analyzed (tail, loin fillet, back fillet and thigh) for their chemical composition, color and yield. The females had higher lipid content (2.40%) and yield of the tail (16.96%) compared to males (1.74% and 15.94%, respectively). The luminosity of the Caiman yacare meat in natura was 50.62 to 53.68, the chroma a* 0.50 to 2.84 and the chroma b* 4.84 to 7.80. It was concluded that the caiman meat has high protein and low fat and it has influence of gender in the tail for lipid content and yield, the females presenting higher values. In the second experiment, the smoked tails fillets of Pantanal caiman (Caiman yacare) were evaluated for physico-chemical aspects, yield and sensory analysis. The tail fillets were smoked with hot smoke and liquid smoke. It was used 20 tail fillets with average weight of 254 g, with 10 repetitions per treatment. The hot-smoked and the liquid-smoke fillets presented respectively, 45.62% and 58.97% moisture, 26.23% and 26.37% protein, 2.60% and 2.09% ash and 21.88% and 8.58% lipids. The yields of the fillets processed by liquid smoke (69.82%) were higher than by hot smoked (58.05%). The major identified fatty acids in tail fillets were palmitic acid, stearic acid, oleic acid and linoleic acid. The hot-smoked tail fillets had significantly higher luminosity (46.71) than those liquid-smoke (44.26). There was no difference for the chroma a* and b*. It was concluded that the liquid-smoked tail fillets presented lower lipid content, higher yield and lower losses, being more advantageous and practical than the hot-smoked ones. In the third experiment the objectives were to evaluate hamburgers prepared from minced caiman meat (Caiman yacare) for chemical composition, color and sensory analysis. The experiment followed a completely randomized design with three treatments (T1 = no smoking; T2 = hot smoked and T3 = liquid smoke). The meat was minced, seasoned and the hamburgers were molded. There was a significant difference for the analysis of centesimal composition; the smoked hamburgers (43.14% and 60.86%) presenting significantly lower moisture than the non-smoked (73.34%). The hot-smoked hamburgers presented lower luminosity (42.05) and higher values of chroma a* (14.65) and b* (28.57) than the other treatments. The hot-smoked products presented more intense pigmentation and the worst acceptance, while the non-smoked and the liquid-smoked hamburgers were well accepted by the judges, showing the feasibility for the development of products from caiman meat. In the fourth experiment the objective was to manufacture flour from the carcasses of caiman and evaluate its physico-chemical composition and acceptance. The carcasses were cooked in water, salt and chimichurri, ground and dried. The non-smoked, hot-smoked and liquid-smoked flours had moisture (3.78%, 4.43%, 10.97%), protein (58.27%, 57.92%, 57.11%), lipids (11.11%, 10.05%, 10.06%) and ash (26.42%, 25.45%, 23.45%), respectively. The calcium content ranged from 6.77% to 7.69%, phosphorus from 3.67% to 4.05% and iron 73.13 to 273.73 ppm/100mg. In the sensory analysis, the smoked flour was accepted by the judges. The flours can be used in the manufacture of products because they presented high protein and mineral content.